Interferenz von Licht macht einzelne unmarkierte Proteine sichtbar - König, Katharina; Gemeinhardt, André; Sandoghdar, Vahid (BioSpektrum, 2019)
iSCAT microscopy is a powerful tool for the optical detection and visualization of small nanoparticles, down to single unlabeled proteins. In this overview, we give an introduction to the method’s principles and benefits and show how it can be applied to monitor protein secretion of single living cells with single-protein sensitivity at millisecond temporal resolution.
CRIS-Team Scopus Importer:2019-12-13

Opportunities and challenges of single protein detection with iSCAT - Nicoli, Francesca; König, Katharina; Dahmardeh, Mahyar; Gemeinhardt, André; Mahmoodabadi, Reza Gholami; Mirzaalian Dastjerdi, Houman; Köstler, Harald; Sandoghdar, Vahid (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
In recent decades large efforts have been made to push optical imaging to the limit, for example for detecting very small proteins. Great achievements have been obtained with fluorescence microscopy, both in terms of localization precision and study of the dynamics of different molecules. Despite the constant improvements, fluorescence-based methods suffer from intrinsic limitations, such as the finite number of emitted photons and photo damage, which limits the temporal resolution and the duration of a measurement. Furthermore, if the molecule of interest is intrinsically non-fluorescent, it has to be labelled with a suitable fluorophore, which in case of biological molecules could interfere with their activity and behavior.
CRIS-Team Scopus Importer:2019-11-15

Visualizing cellular secretion with single-protein sensitivity via interferometric scattering microscopy (iSCAT) - Gemeinhardt, André; König, Katharina; Nicoli, Francesca; Dahmardeh, Mahyar; Sandoghdar, Vahid (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Proteins are involved in a large number of biological processes. Apart from the field of proteomics, where ensemble studies of the entire set of proteins present in a system are carried out, detection and analysis of single proteins has become a vibrant field of research. Particularly, the study of proteins that are secreted from cells into the extracellular space is an important topic with wide implications for basic intercellular interactions and immunology. Secretory proteins are responsible for a vast amount of cellular functions involving migration, wound healing, immunological response, or intercellular communication. Challenges in the traditional methods such as immunoassays, Western blotting, mass spectrometry, or fluorescence microscopy are the need for labeling (with immunological complements, isotopes, or fluorescent markers) and the necessary processing and separation steps that hinder high temporal resolution in dynamic studies. Today, none of the existing techniques is able to detect single proteins secreted from living cells at subsecond temporal resolution without the need for labeling.
CRIS-Team Scopus Importer:2019-11-15

Visualizing Single-Cell Secretion Dynamics with Single-Protein Sensitivity - McDonald, Matthew; Gemeinhardt, André; König, Katharina; Piliarik, Marek; Schaffer, Stefanie; Völkl, Simon; Aigner, Michael; Mackensen, Andreas; Sandoghdar, Vahid (Nano Letters, 2017)
Cellular secretion of proteins into the extracellular environment is an essential mediator of critical biological mechanisms, including cell-to-cell communication, immunological response, targeted delivery, and differentiation. Here, we report a novel methodology that allows for the real-time detection and imaging of single unlabeled proteins that are secreted from individual living cells. This is accomplished via interferometric detection of scattered light (iSCAT) and is demonstrated with Laz388 cells, an Epstein-Barr virus (EBV)-transformed B cell line. We find that single Laz388 cells actively secrete IgG antibodies at a rate of the order of 100 molecules per second. Intriguingly, we also find that other proteins and particles spanning ca. 100 kDa-1 MDa are secreted from the Laz388 cells in tandem with IgG antibody release, likely arising from EBV-related viral proteins. The technique is general and, as we show, can also be applied to studying the lysate of a single cell. Our results establish label-free iSCAT imaging as a powerful tool for studying the real-time exchange between cells and their immediate environment with single-protein sensitivity.
EVALuna2:25781